The man who saw tomorrow - Guenette, Robert (Philippines : Warner Home Video.)
The assassinations of Presidents Lincoln and Kennedy. The rise and fall of Napoleon, Edward VIII's abdication of the throne. A German tyrant - identified as Hitler - and his reign of terror. Khomeini's ascent to power in Iran... Qaddafi in Libya... and Hussein in Irag. We know these events through history books and the news media. But - just maybe - one man knew of them centuries in advance! Award-winning filmmaker David L. Wolper combines live action, feature-film excerpts, newsreel footage and authorative interviews for the The Man Who Saw Tomorrow, a fascinating recreation of the life and prophecies of the 16th-century Medici court seer, Michael de Nostradamus. Narrated by Orson Welles, this timely film takes you from events that occured as Nostradamus had predicted centuries earlier to his terrifying forecasts for our century... and the promise of an unparalleled era of peace. Are his predictions hoaxes or warnings? As with all mysteries, you must reach you own conclusions.